The effects of testosterone on immune function in quail selected for divergent plasma corticosterone response - Roberts, Mark L. (2009)
The immunocompetence handicap hypothesis (ICHH) suggests that the male sex hormone testosterone has a dual effect; it controls the development and expression of male sexually selected signals, and it suppresses the immune system. Therefore only high quality males are able to fully express secondary sexual traits because only they can tolerate the immunosuppressive qualities of testosterone. A modified version of the ICHH suggests that testosterone causes immunosuppression indirectly by increasing the stress hormone corticosterone (CORT). Lines of Japanese quail (Coturnix japónica) selected for divergent responses in levels of plasma CORT were used to test these hypotheses. Within each CORT response line (as well as in a control stock) we manipulated levels of testosterone in castrated quail by treatment with zero (sham), low or high testosterone implants, before testing the birds' humoral immunity and phytohaemagglutinin (PHA)-induced immune response, as well as body condition. The PHA-induced response was not significantly affected by CORT selected line, testosterone treatment or their interaction. There was, however, a significant effect of CORT line on humoral immunity in that the control birds exhibited the greatest antibody production, but there was no significant effect of testosterone manipulation on humoral immunity. The males in the sham implant treatment group had significantly greater mass than the males in the high testosterone group, suggesting a negative effect of high testosterone on general body condition. We discuss these results in the context of current hypotheses in the field of sexual selection.